Vračanje na delo po nezgodni možganski poškodbi pri bolnikih po zaključeni rehabilitaciji - Grabljevec, Klemen (Rehabilitacija (Ljubljana), 2017)
Introduction: The majority of patients with mild brain injuries recover rapidly and return to their premorbid activities; a small group may continue to experience cognitive, emotional and physical impairments. In contrast, a large proportion of moderately to severely brain-injured patients are left with permanent impairments that profoundly affect their ability for self-care, mobility, and reintegration to society. Return-to-work ratio after traumatic brain injury is varies greatly between different injury-severity groups, ranging from 0 % to 84 %. The main unfavourable factors for return to work are discussed in the paper, as well the results of a Slovenian pilot study about return to work ratio among traumatic brain injury patients. Methods: We sent a survey questionnaire to 108 patients hospitalised between 2008 and 2010 at the University Rehabilitation Institute in Ljubljana after mild, moderate and severe traumatic brain injury (Glasgow Coma Scale 3 % 15). All the persons invited to participate in the survey were regularly employed before sustaining traumatic brain injury. We received answers from 78 persons. Among the received questionnaires, we determined the extent and format of individual employment after return to work. Results: Thirty-four respondents (44 %) were retired because of injury consequences and 22 (28 %) kept the employment after rehabilitation to various extent and in various format. Eighteen respondents (23 %) were unemployed at the time of the survey and 4 (5 %) retired regularly.
Keywords: Brain Injuries, Traumatic; možganske poškodbe; poklicna rehabilitacija; Rehabilitation, Vocational; return to work; traumatic brain injury; vocational rehabilitation; vračanje na delo